Audience Experience on the Meaning of the Film "Petualangan Sherina 2": A Phenomenological Approach (Cinematology: Journal Anthology of Film and Television Studies, 2025)
This study explores audience experiences in interpreting the film Petualangan Sherina 2 through a phenomenological approach. The research is motivated by the return of Petualangan Sherina after 23 years since its original release in 2000, which marked a pivotal moment in the resurgence of the Indonesian film industry. The study focuses on a group of viewers who had watched the first film during their childhood and have now watched its sequel as adults, particularly those aged between 32 and 38 years. Through in-depth interviews with 10 participants who met these criteria, the study finds that Petualangan Sherina 2 not only evokes nostalgia and childhood memories but also serves as a medium for self-reflection and the reinterpretation of life experiences. Viewers experience strong episodic and associative memories, as elements of the film—such as characters, music, and narrative—trigger recollections and emotions associated with their past. Furthermore, the film functions as an intergenerational bridge, as many first-generation viewers brought their children to watch the film, creating a new shared cultural experience. Employing a phenomenological approach, this study highlights how popular art can act as a catalyst for self-reflection, identity continuity, and the strengthening of emotional ties between individuals and their past experiences. The findings of this research are expected to contribute to the fields of film studies, psychology, and cultural communication in Indonesia.